New species of Dahlibruchus Bridwell, 1931 (Coleoptera: Bruchidae) from an archaeological site in Texcoco, Mexico, with some comments about history of the site and bionomics of the insect - Romero Nápoles, Jesús; Romero Ramírez, María (Instituto de Ecología, A.C., 2011)
A new species of the Dahlibruchus genus is described and information is given about its bionomics and host plants, also are mentioned general aspects about the archeological site where the insect was found.